GENDER INEQUALITY IN ELIZABETH RUDNICK’S NOVEL MULAN - Massya Yuridha (Universitas Islam Sumatera Utara, 2023)
This study is aimed at analyzing gender inequality in Elizabeth Rudnick’s Novel Mulan. This study is focused on the phenomena of gender inequality in the novel, and the gender inequality seen through socio-cultural context. Mulan tells about of a young Chinese woman, a female warrior from the period of the Northern and Southern Chinese dynasties. She disguises herself as a man to fight. She replaces her father in a war. As the first child, Mulan is burdened with the tasks of bringing honor to her family; while, at that time, the kingdom does not allow a woman to join the war. Such part of the story in the novel portrays gender inequality. In the study, the descriptive qualitative method is applied. The result of this research shows that the phenomena of gender inequality cover gender violence against women presented in the novel. Besides, the gender inequality can be seen through socio-cultural context in the novel. It can be concluded that gender difference between women and men can be found in the novel. It occurs in social and cultural context in the novel.